Instrument-assisted soft tissue mobilization improves physical performance of young male soccer players - Kim, J.; Yim, J. (International Journal of Sports Medicine, 2018)
This study aimed to examine the effects of a rehabilitation exercise combined with instrument-assisted soft tissue mobilization on the isokinetic power, muscle fatigue, and fitness of soccer players. An interventional study design was used to assess 40 subjects aged 15-17 years. Twenty participants each in instrument-assisted soft tissue mobilization and control groups completed several tests to determine player development. The results showed significant differences between the two groups with respect to the isokinetic power of the ankle (i. e., dorsiflexion, peak torque body weight at the right- and left-foot angular velocities of 30°/s and 120°/s; plantar flexion, peak torque body weight at the right- and left-foot angular velocities of 30°/s and 120°/s) and knee (extension, right peak-torque body weight at 60°/s and 180°/s and left peak-torque body weight at 60°/s; flexion, right and left peak-torque body weight at 60°/s and 180°/s), muscle fatigue, and physical fitness (P<0.05). Instrument-assisted soft tissue mobilization in soccer players suggests that the characteristics of athletic performance may be improved by decrease in fatigue and increase in fitness and muscle power. Therefore, we suggest instrument-assisted soft tissue mobilization for soccer players to increase their performance.